Herpes simplex virus infection. The roles of T4ymphocytes in host responses - M. Cholis, M. Cholis (Universitas Gadjah Mada, 1996)
T-lymphocytes are the most important component of the immune response to control recurrent infections. T-Iumphocytes of CD4+ and CD8 + recognize a variety of viral proteins and produce lymphokines with antiviral and immunomodulatory effects. Both CD4+ and CIDER- bearing T-cells can kill HSV infected host cells. The relation between specific T-cells responses and severity of HSV disease have not been consistently detected. Interaction between T-cells responses and HSV and host cells result in a dynamic state of latency. HSV has evolved special mechanisms for evasion of host immunity. Reactivation can result in recurrences with the implication of transmission and/or disease. Molecular definition of T-cell responses for HSV may lead to immunological intervention to prevent HSV disease. Impaired T-cell immunity should be considered as a risk factor for severe infections.Key words: herpes simplex - T-cell role - latency - immunocompromised - vaccine